Diseño de tácticas comerciales para un sistema de distribución de combustibles - Gómez Robinson, Idania (2010)
This paper develops an analysis of ABC company processes dedicated to the transportation, storage and marketing of fuels in the country. To develop this Project, focused on the study of processes, analysis of the value chain and the time lost in the supply center. The supply center has shown problems with the integration to the final consumer with service stations themselves. The overall objective of this project is to streamline operations in the supply center and hit with it until the business themselves. The methodology used to develop the project starts with defining the scope of activity mapping, choice of the flow of value to understand how the current operations from supplier to final consumer. Then he designed the current state map to target value as it flows and what problems we have while filling the tank cars. Through it you want to increase the productivity of the center, and improving the operation will result is better use of resources.